2007
DOI: 10.1016/j.otohns.2007.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Exclusively Endoscopic Surgery for Juvenile Nasopharyngeal Angiofibroma

Abstract: It seems to be appropriate to reevaluate the surgical limits of endoscopic surgery for resecting JNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 16 publications
0
40
1
Order By: Relevance
“…A number of authors have compared endoscopic resection of a juvenile angiofibroma with the open surgical approaches and have found endoscopic resection to be safe and effective, with similar recurrence rates. 17,21 Furthermore, patients undergoing endoscopic resection demonstrated fewer complications, less operative blood loss, and shorter hospital stays. 17 Tumor resection in our series was from an endoscopic approach in 7 cases and from a standard open surgical approach in 2 cases.…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors have compared endoscopic resection of a juvenile angiofibroma with the open surgical approaches and have found endoscopic resection to be safe and effective, with similar recurrence rates. 17,21 Furthermore, patients undergoing endoscopic resection demonstrated fewer complications, less operative blood loss, and shorter hospital stays. 17 Tumor resection in our series was from an endoscopic approach in 7 cases and from a standard open surgical approach in 2 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic surgery is becoming a promising approach for early stage growth mainly I and II. The main advantage of endoscopic surgery is the possibility of obtaining a broad view of the lesion and its anatomic relationship with adjacent structures, promoting more accurate, complete dissection and better control of bleeding [9][10][11]. Other advantages include less surgical time, hospitalization, absence of visible scars, avoids complication such as epiphora, dysesthesia, trismus, and craniofacial deformities [10,[12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study complete tumour removal was achieved in all the operated cases. Preoperation embolization results in less intraoperative blood loss (\1000 ml) and lower subsequent requirement for blood transfusion [11][12][13]. In our study it was found very effective since the blood loss estimated was 300-1200 ml (average 630 ml).…”
Section: Discussionmentioning
confidence: 46%